The Semantic Meaning of the Terms of Religious Moderation in the Qur'an from the Perspective of Muqotil ibn Sulaiman Al-Balkhy/ المعنى الدلالي لتواسط الدّيني في القرآن من وجهة نظر مقاتل ابن سليمان البلخي - Isbah, Faliqul; Fauzi, Rizki; Rosyid, M. Fairuz (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This study aims to examine the meaning of the verses of the Qur'an related to Religious Moderation from the perspective of Muqotil ibn Sulaiman Al-Balkhy which focuses on four words, namely: al-din, al-kufr, al-syirk and al-jihad. The choice of these four terms is because they are closely related to the discussion of religious moderation in which there are certain groups who generalize the meaning of the term textually, even though every word in the Qur'an has several alternative meanings that vary. This study uses a qualitative method of library research or library research. The results of this study are that the four terms have various meanings, namely: the word al-Din has five meanings: Tawhid, Calculation (Charity), Law, Religion and Belief. The word al-Kufr has four meanings: denying the oneness of Allah, denying argument, denying favors and breaking away. The word al-Shirk has three meanings: associating partners with Allah with something else, shirk by not worshiping and showing off. The word al-Jihad has three meanings: speech, war with weapons and Charit